1995
DOI: 10.1128/jb.177.22.6625-6629.1995
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural diversity of the cellulase complexes of Clostridium papyrosolvens C7

Abstract: Transmission electron microscopy was used to investigate the ultrastructural features of diverse cellulase and cellulase-xylanase multiprotein complexes that are components of the cellulase-xylanase system of Clostridium papyrosolvens C7. The multiprotein complexes were separated by anion-exchange chromatography into seven biochemically distinguishable fractions (F1 to F7). Most individual F fractions contained, in relatively large numbers, an ultrastructurally recognizable type of particle that occurred only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…Moreover, the enzymatic activities in the fractions were also different. These results indicated that C. cellulovorans grown with pectin produced heterogeneous cellulosomes, as has been shown with C. papyrosolvens C7 cellulosomes (17,18).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Moreover, the enzymatic activities in the fractions were also different. These results indicated that C. cellulovorans grown with pectin produced heterogeneous cellulosomes, as has been shown with C. papyrosolvens C7 cellulosomes (17,18).…”
Section: Discussionsupporting
confidence: 58%
“…So far, it has been observed that carbon sources in the medium have an effect on enzymatic activity and enzyme composition (15,23). Pohlschroder et al reported that Clostridium papyrosolvens C7 produces at least seven different forms of cellulosomes and that each type of cellulosome has a different enzymatic activity (17,18). These results indicate that Clostridium species actually produce heterogeneous cellulosomes and that the enzymatic activity of each cellulosome depends on its subunit composition.…”
mentioning
confidence: 92%
“…The different subunits in these populations represented the presence of a large number of different cellulosomal enzymes. Furthermore, when these populations were examined by transmission electron microscopy, each population had a distinct morphology, again indicating a difference in subunit composition of these complexes (51). It seems clear at this time that cellulosomes are heterogeneous in enzymatic subunit composition and that in nature this may help the bacteria to degrade a complex substrate such as plant cell walls very efficiently.…”
Section: Heterogeneity Of Cellulosomesmentioning
confidence: 99%
“…In C. papyrosolvens, a mesophilic anaerobe, the cellulase system (53) can be fractionated by ion-exchange chromatography into seven high-molecular-weight multiprotein complexes, with the molecular weights ranging from 500,000 to 600,000. Each complex has a different ultrastructure (269) and a unique profile of enzymatic activities (270). The common protein appearing in each fraction is a glycoprotein (M r ϭ 125,000) that lacks any enzymatic activity.…”
Section: Cellulosome Structurementioning
confidence: 99%